Field, Thomas; Krepp, Stella y Vanni Pettina (eds.). Latin America and the Global Cold War. Chapel Hill: University of North Carolina Press, 2020, 440 pp. - Adrianzén Ponce, Cayetana (2020)
No presenta resumen